Importance of the Activation Sequence of the His or Right Bundle for Diagnosis of Complex Tachycardia Circuits. (4th October 2021) - Viswanathan, Mohan N.; Julie He, Beixin; Sung, Raphael; Hoffmayer, Kurt S.; Badhwar, Nitish; Lee, Adam; Goldberger, Jeffrey J.; Hsia, Henry H.; Jackman, Warren M.; Scheinman, Melvin M.
Abstract : Supplemental Digital Content is available in the text. Abstract : In this review, we emphasize the unique value of recording the activation sequence of the His bundle or right bundle branch (RB) for diagnoses of various supraventricular and fascicular tachycardias. A close analysis of the His to RB (H-RB) activation sequence can help differentiate various forms of supraventricular tachycardias, namely atrioventricular nodal reentry tachycardia from concealed nodofascicular tachycardia, a common clinical dilemma. Furthermore, bundle branch reentry tachycardia and fascicular tachycardias often are included in the differential diagnosis of supraventricular tachycardia with aberrancy, and the use of this technique can help the operator make the distinction between supraventricular tachycardias and these other forms of ventricular tachycardias using the His-Purkinje system. We show that this technique is enhanced by the use of multipolar catheters placed to span the proximal His to RB position to record the activation sequence between proximal His potential to the distal RB potential. This allows the operator to fully analyze the activation sequence in sinus rhythm as compared to that during tachycardia and may help target ablation of these arrhythmias. We argue that 3 patterns of H-RB activation are commonly identified—the anterograde H-RB pattern, the retrograde H-RB (right bundle to His bundle) pattern, and the chevron H-RB pattern (simultaneous proximal His and proximal RB activation)—and specific arrhythmias tend to be associated with specific H-RB activation sequences. We show that being able to record and categorize this H-RB relationship can be instrumental to the operator, along with standard pacing maneuvers, to make an arrhythmia diagnosis in complex tachycardia circuits. We highlight the importance of H-RB activation patterns in these complex tachycardias by means of case illustrations from our groups as well as from prior reports.